2011
DOI: 10.1016/j.worlddev.2010.09.016
|View full text |Cite
|
Sign up to set email alerts
|

The Forgotten Property Rights: Evidence on Land Use Rights in Vietnam

Abstract: Studies of land property rights usually focus on tenure security and transfer rights.Rights to determine how to use the land are regularly ignored. However, user rights are often limited. Relying on a unique Vietnamese panel data set at both household and plot level, we show that crop choice restrictions are widespread and prevent crop diversification. Restrictions do not decrease household income, but restricted households work harder, and there are indications that they are supplied with higher quality input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 23 publications
0
60
1
Order By: Relevance
“…At the plot level in Vietnam, Markussen et al [44] conclude that the land title is exogenous. However, it is still plausible that land tenure is endogenous.…”
Section: Econometric Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the plot level in Vietnam, Markussen et al [44] conclude that the land title is exogenous. However, it is still plausible that land tenure is endogenous.…”
Section: Econometric Specificationmentioning
confidence: 99%
“…Although various studies have investigated the impacts of this land reform in Vietnam [33,39,41,43,44], only few of them deal with soil conservation at the household level [45]. This is partly due to the lack of reliable household data.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on land ownership rights have focused on tenure security and land transfer rights (Markussen, Tarp and Van den Broeck, 2011). The author claim that the rights of land users are limited.…”
Section: Gender and Land Rightsmentioning
confidence: 99%
“…The author claim that the rights of land users are limited. Using panel data on farm households in Vietnam, Markussen et al (2011) showed that restrictions on crop choices limit the diversification of crops. These restrictions limit the labor supply of households.…”
Section: Gender and Land Rightsmentioning
confidence: 99%
“…Individual rights may also improve productivity through easing access to credit, since land is an excellent form of collateral when borrowing money from the bank (Markussen 2008). In socialist countries undergoing rapid transitions, land titling has led to increased food security, although crop variation may be an issue, depending upon state policies (Markussen et al 2011). Improved transferability rights of land have also led to a significant increase in activity in both rental and sales markets.…”
Section: Understanding Property Rights and The Vietnamese Contextmentioning
confidence: 99%